2018
DOI: 10.4136/ambi-agua.2151
|View full text |Cite
|
Sign up to set email alerts
|

Insalubrious touristic environments and schistosomiasis transmission in Pernambuco, Brazil

Abstract: This study sought to identify and spatialize the risk of transmission of Manson’s schistosomiasis at localities in Pernambuco, Brazil that are used for tourist leisure activities and have freshwater environments that are inhabited by the snail that transmits this disease. In order to accomplish this, malacological surveys were conducted at the selected localities between May and December 2016, in order to identify and georeference the breeding sites and foci of schistosomiasis-transmitting mollusks of the genu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
2
0
1
Order By: Relevance
“…A irradiação dos esgotos nos rios, lagoas e valas possibilita a criação de ambientes insalubres que são favoráveis à transmissão da doença. O foco da doença no estado é localizado na região metropolitana, na zona da mata e nas cidades vizinhas ao agreste pernambucano 15 .…”
Section: Discussionunclassified
“…A irradiação dos esgotos nos rios, lagoas e valas possibilita a criação de ambientes insalubres que são favoráveis à transmissão da doença. O foco da doença no estado é localizado na região metropolitana, na zona da mata e nas cidades vizinhas ao agreste pernambucano 15 .…”
Section: Discussionunclassified
“…Transmission occurs when infected individuals lay their faeces with parasite eggs in water bodies infested by snails, which become infected by miracidia that hatch from the eggs. Infected snails release cercariae that can penetrate the skin of humans, evolving to schistosomules that will develop to adult worms, which copulate and lay eggs in the mesenteric venous plexus (Barbosa et al, 2018;Carvalho et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The Northeast region is one of the favorite travel destinations in Brazil because of its stunning coastline and rich seafood cuisine. One important state in the region is Pernambuco, where tourists and residents are usually attracted by its recreational waters and beach-related activities (20). One study found NoV prevalence in humans in Pernambuco to be 15% (21).…”
Section: Introductionmentioning
confidence: 99%